Local synthesis of hepcidin in the anterior segment of the eye: A novel observation with physiological and pathological implications. (January 2020) - Ashok, Ajay; Chaudhary, Suman; McDonald, Dallas; Kritikos, Alexander; Bhargava, Disha; Singh, Neena
Abstract: Purpose: The avascular cornea, trabecular meshwork (TM), and lens obtain iron, an essential biometal, from the aqueous humor (AH). The mechanism by which this exchange is regulated, however, is unclear. Recently we reported that non-pigmented ciliary epithelial cells express ferroportin (Fpn) (Ashok, 2018b), an iron export protein modulated by hepcidin, the master regulator of iron homeostasis secreted mainly by the liver. Here, we explored whether ciliary epithelial and other cells in the anterior segment synthesize hepcidin, suggesting local regulation of iron exchange at this site. Methods: Human and bovine eyes were dissected to isolate the ciliary body (CB), corneal endothelial (CE), TM, lens epithelial (LE), and outer epithelial cell layer of the iris. Total mRNA and protein lysates were processed to evaluate the synthesis and expression of hepcidin, the iron regulatory peptide hormone, Fpn, the only known iron export protein, ceruloplasmin (Cp), a ferroxidase necessary for iron export, transferrin receptor (TfR), a major iron uptake protein, and ferritin, a major iron storage protein. A combination of techniques including reverse transcription polymerase chain reaction (RT-PCR) of total mRNA, Western blotting of protein lysates, and immunofluorescence of fixed tissue sections were used to accomplish these goals. Results: RT-PCR of isolated tissue samples revealed hepcidin-specific mRNA in the CB, TM, CE, and LE of the bovine eye. Western blotting of protein lysates from these tissues showed reactivity for hepcidin, Fpn, ferritin, and TfR. Western blotting and immunohistochemistry of similar tissues isolated from cadaveric human eyes showed expression of hepcidin, Fpn, and Cp in these samples. Notably, Fpn and Cp were expressed on the basolateral membrane of non-pigmented ciliary epithelial cells, facing the AH. Conclusions: Synthesis and expression of hepcidin and Fpn in the ciliary epithelium suggests local regulation of iron transport from choroidal plexus in the ciliary body to the AH across the blood-aqueous barrier. Expression of hepcidin and Fpn in CE, TM, and LE cells indicates additional regulation of iron exchange between the AH and cornea, TM, and lens, suggesting autonomous regulation of iron homeostasis in the anterior segment. Physiological and pathological implications of these observations are discussed. Highlights: Hepcidin is synthesized locally by cells of the anterior eye segment (AS). Co-expression of ferroportin suggests autonomous regulation of iron in the AS. Hepcidin is upregulated by IL6, implicating iron in inflammation of the AS.